2013
DOI: 10.1111/bju.12230
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in matrix metalloproteinases (MMPs) and tissue inhibitors of MPs (TIMPs), and bladder cancer susceptibility

Abstract: Objectives• To elucidate genetic polymorphisms of the matrix metalloproteinases (MMPs) MMP1 (rs1799750), MMP2 (rs243865), MMP9 (rs3918242), MMP12 (rs2276109) and tissue inhibitors of MMPs (TIMPs) TIMP1 (rs2070584) and TIMP3 (rs9619311) genes that may be involved in susceptibility to bladder cancer (BC). Patients and Methods• We enrolled 241 patients with BC and 199 controls.• Genomic DNA samples were extracted from peripheral blood and polymorphisms were analysed by high-resolution melting analysis and by real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 53 publications
2
43
2
1
Order By: Relevance
“…They concluded that the combined genotype carrying MMP2 rs243865 allele T with MMP9 rs3918242 allele T was found to increase bladder cancer risk. 15 These results are the opposite to the previously mentioned Asian based metaanalysis. 14 According to the db SNP and HapMap data on rs243865 frequency in genetically different populations, the C allele is more common in Caucasian populations.…”
Section: Discussionmentioning
confidence: 69%
“…They concluded that the combined genotype carrying MMP2 rs243865 allele T with MMP9 rs3918242 allele T was found to increase bladder cancer risk. 15 These results are the opposite to the previously mentioned Asian based metaanalysis. 14 According to the db SNP and HapMap data on rs243865 frequency in genetically different populations, the C allele is more common in Caucasian populations.…”
Section: Discussionmentioning
confidence: 69%
“…A previous study conducted transient transfections and DNA-protein interaction assays, and found that the T allele of MMP9 -1562 C>T had higher promoter activity compared with the C allele due to the binding of a transcriptional repressor (Zhang et al, 1999). Several previous studies found that the MMP9 -1562 C>T polymorphism was associated with an increased risk of lung and bladder cancer and ESCC (Vairaktaris et al, 2008;Lei et al, 2009;Wieczorek et al, 2013). Lei et al (2009) reported a meta-analysis of eight case-control studies, and discovered that the MMP9 -1562 C>T polymorphism was associated with lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Lei et al (2009) reported a meta-analysis of eight case-control studies, and discovered that the MMP9 -1562 C>T polymorphism was associated with lung cancer risk. Wieczorek et al (2013) reported that the MMP9-1562 T allele was linked with increased bladder cancer risk. One study reported that the MMP9-1562 C>T polymorphism was associated with increased risk of ESCC, and conversely, another report demonstrated no association (Zhou et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We also found only one Chinese article in the WanFang database. As a result, 12 case-control articles were included in our meta-analysis: (Hirata et al, 2004;Zhong et al, 2005;Kader et al, 2006;Albayrak et al, 2007;Piccoli et al, 2007;Tasci et al, 2008;Tsuchiya et al, 2009;Srivastava et al, 2010aSrivastava et al, , 2010bWieczorek et al, 2013Wieczorek et al, , 2014Srivastava et al, 2013a) (Fig. 1).…”
Section: Eligible Studiesmentioning
confidence: 99%
“…A quantitative synthesis to accumulate data from different studies is needed to provide better evidence on these associations. Here, in this report, we performed a meta-analysis of 12 publications to estimate the effect of eight polymorphisms: MMP1 -1607 1G/2G (Hirata et al, 2004;Kader et al, 2006;Albayrak et al, 2007;Piccoli et al, 2007;Tasci et al, 2008;Tsuchiya et al, 2009;Srivastava et al, 2010a;Wieczorek et al, 2013), MMP2 -1306 C/T (Zhong et al, 2005;Kader et al, 2006;Srivastava et al, 2013a;Wieczorek et al, 2013), MMP3 (45E/K) G/A (Kader et al, 2006;Srivastava et al, 2010b), MMP7 -181 A/G (Srivastava et al, 2010a;Wieczorek et al, 2014), MMP9 -1562 C/T (Zhong et al, 2005;Kader et al, 2006;Wieczorek et al, 2013), MMP9 (279R/Q) A/G (Kader et al, 2006;Tasci et al, 2008;Srivastava et al, 2010b), and MMP9 (574R/P) T/C (Kader et al, 2006;Srivastava et al, 2010b), MMP9 (668Q/R) A/G (Kader et al, 2006;Srivastava et al, 2010b) on urinary cancer risk.…”
Section: Introductionmentioning
confidence: 99%